Developing Multiple Paired Comparisons Model for Analysis of Variance Technique - Abbood M. Jameel (Cihan University-Erbil Journal of Humanities and Social Sciences)
A class of multiple paired comparison models can be developed for taste-testing experiments to evaluate several objects on a seven-point preference scale. This allows for calculating a preference score for each object using the two-way analysis of variance technique (ANOVAT). The primary objective of this research is to distinguish between different types of objects or items by calculating degrees of preference (scores), denoted as S j. These objects, represented by L, are evaluated through paired comparisons. Specifically, we consider six types of potato chips, labeled as A, B, C, D, E, and F. Each pair of chips is presented to two equal groups (2n) of judges or referees, where each group consists of n = 15 individuals. The goal is to determine which object or item is favored over the other. In these comparisons, judges or referees answer the question: Which do you prefer, Object Oj or Object Ok? Their responses are recorded on a seven-point preference scale. The data collected from these paired comparisons are organized using a tabulation method, as demonstrated in Table I. Various statistical methods, including the developed multiple paired comparison model and the two-way ANOVAT, were employed for analysis. The results, summarized in Table IV, indicate that potato chip type B is the most preferred, followed by types D and C, respectively. Type F was found to be the least preferred.